2018
DOI: 10.18051/univmed.2018.v37.105-114
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycle accident injuries are more severe than other land transportation injuries

Abstract: Background<br />Injuries due to traffic accidents are the leading cause of death and disability, especially in developing countries. The proportion of injuries in Indonesia tends to increase. The cause of the injury is dominated by motorcycle accidents (70-85%). The aim of this study was to compare the severity of motorcycle injuries with that of other land transportation injuries in Indonesia. <br /><br />Methods<br />A study of a cross-sectional design was performed involving 15,849 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Motorcycle accidents are very dangerous for drivers in various parts of the world, especially in Asia 11 . In Indonesia, research in 33 provinces, concluded that the causes of injuries due to traffic accidents were dominated by motorbikes 12 . Indonesian National Police's data shows the number of accidents continues to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Motorcycle accidents are very dangerous for drivers in various parts of the world, especially in Asia 11 . In Indonesia, research in 33 provinces, concluded that the causes of injuries due to traffic accidents were dominated by motorbikes 12 . Indonesian National Police's data shows the number of accidents continues to increase.…”
Section: Introductionmentioning
confidence: 99%